Understanding exposure : how to shoot great photographs with any camera - Peterson, Bryan (Berkeley, California : AmPhoto Books, 2016)
Veteran photographer Bryan Peterson demystifies complex concepts of exposure in photography by explaining the fundamentals of light, aperture, shutter speed, and how they interact with and influence one another. This book explains how to get or lose sharpness and contrast in images, freeze in action, and take the best meter readings while also exploring filters, flash, and light. This fourth edition includes all new images as well as an expanded section on flash, tips for using colored gels, and advice on shooting star trails.
Introduction 1 -- Defining Exposure What Is Meant by Exposure? 8 -- The Photographic Triangle 10 -- The Heart of the Triangle: The Light Meter 16 -- White Balance 19 -- Six Correct Exposures Versus One Creatively Correct One 24 -- Finding Creative Exposure Options 28 -- Aperture Aperture and Depth of Field 32 -- Storytelling Apertures 36 -- Isolation or Singular-Theme Apertures 48 -- "Who Cares?" Apertures 54 -- Aperture and Macro Photography 58 -- Shutter Speed The Importance of Shutter Speed 64 -- The Right Shutter Speed for the Subject 66 Freezing Motion 68 -- Panning 73 -- Implying Motion 76 -- Implying Motion with Stationary Subjects 80 -- Making "Rain" 83 -- Light The Importance of Light: The Importance of Exposure 86 -- The Best Light 88 -- Frontlight 92 -- Overcast Frontlight 95 -- Sidelight 98 -- Backlight 102 -- Exposure Meters 106 -- 18% Reflectance 110 -- The Gray Card 112 -- The Sky Brothers 113 -- Mr. Green Jeans (The Sky Brothers' Cousin) 116 -- Night and Low-Light Photography 118 -- Flashlights and Starlight 124 -- Light Painting 126 -- Special Techniques Polarizing Filters 132 -- Graduated Neutral-Density Filters 134 -- Multiple Exposures 136 -- Electronic Flash The Photographic Triangle and Flash 142 -- The Three Factors for Correct Flash Photography Exposure 144 -- The Dangers of Becoming a Flashaholic 148 -- The Limitations of Your Teenie-Weenie Pop-Up Flash 150 -- Powering Down the Flash 152 -- Flash as a Fill Light 153 -- Wireless Flash 158 -- Colored Gels 162 -- Rear Curtain Sync 165 -- Index 168.
Includes index.
Keywords: PHOTOGRAPHY